Biofilm Formation and pH Indication: Exploring the Potential of Anthocyanin Extracted from Grape Skin - Hemandeep Kaur; Dr. Puneet; Harpreet Kaur (International Journal of Scientific Research in Science and Technology, 2025)
This study developed a biopolymer-based pH-sensitive biofilm using sodium alginate, starch, calcium chloride, and anthocyanin extracted from black grapes skin. Total Anthocyanin Content (TAC) was measured using a pH differential method, and UV-Vis spectrophotometry assessed anthocyanin response across pH levels 1-14. The biofilm's stability was evaluated via moisture content analysis (initial weight: 120 g; dry weight: 22 g), water resistance, and long-term storage. The biofilm showed strong stability and pH sensitivity, displaying various colours across pH levels, from red at pH 1 to yellow-green at pH 14. Water resistance testing revealed minor anthocyanin leaching over 24 hours due to hydrophilic properties of starch. These findings suggest that this biofilm could serve as an eco-friendly pH indicator with potential applications in intelligent packaging.
Keywords: biofilm; anthocyanin; pH-indicator; sodium alginate; total anthocyanin content (TAC)